Reliability and validity of the strain gauge "GSTRENGTH" for measuring peak force in the isometric belt squat at different joint angles - Varela-Olalla, D.; Balsalobre-Fernández, C.; Romero-Moraleda, B.; Jiménez-Sáiz, S. L. (Sensors, 2024)
Since isometric training is gaining popularity, some devices are being developed to test isometric force as an alternative to the more expensive force plates (FPs); thus, the aim of this study was to test the reliability and validity of "GSTRENGTH" for measuring PF in the isometric belt squat exercise. Five subjects performed 24 contractions at three different knee angles (90°, 105° and 120°) on two occasions (120 total cases). Peak force data were measured using FPs and a strain gauge (SG) and analyzed by Pearson`s product-moment correlation coefficient, ICCs, Cronbach`s alpha, a paired sample t-test and Bland-Altman plots. Perfect or almost perfect relationships (r: 0.999-1) were found with an almost perfect or perfect level of agreement (ICCs: 0.992-1; a: 0.998-1). The t-test showed significant differences for the raw data but not for the predictions by the equations obtained with the SG values. The Bland-Altman plots, when significant, showed trivial to moderate values for systematic bias in general. In conclusion, "GSTRENGTH" was shown to be a valid alternative to FPs for measuring PF.